Os efeitos da gest??o de portf??lio aplicada nas adminitra????es p??blicas municipais - Jesus, Luiz Am??rico de (2020)
Management techniques from private sector are often used on public sector based on NPM (New Public Management) theory. On private sector the modern portfolio management theory is consolidated, this theory had evolved from financial area, inside project management environment it was adapted as PPM (Project Portfolio Management), focused on maximizing resource application efficiency as well risk management in order to drive a better return of investment on project portfolio. Once project implementation is a reality inside public administration as well resource limitation and a target to reach higher efficiency level on public services, there are an improvement on PPM applying on public sector. However, in the same way as occurs to the other techniques of NPM, there are a adapting process on private execution techniques when applied to the public environment. That makes some parts on those techniques been applied in lower or higher intensity. This tailor-made form, sometimes, generate different effects to the same theory in the public sector related to the original conception from the private sector. Based on that, this research proposes to investigate the following question: how does project portfolio management affect municipal administrations? To answer this question, this dissertation analyzed practices of project management, organized as a structured portfolio or not, into some municipalities in the state of S??o Paulo in order to identify patterns on portfolio management practices which are been applied on their administration and which results are pointed out by those administrations related to structuring , execution and maintenance of public projects. The methodology applied to seek the proposed objective was In-Depth Interviews with managers from execution and or controlling areas from each municipality plus secondary data collecting from city accountability documents, local legislation and public informs into official websites. The data was collected and analyzed via ATLAS TI. 5 cities from state of S??o Paulo, placed on 3 macroregion, with different economic and political matrix were analyzed. This research allowed us to raise 5 propositions that connect project portfolio management, through the multi-annual plan and the legislation related to the construction of the municipal budget, with the capacity for deliveries, fundraising and dialogue with the different stakeholders of the municipality, which allow to advance in the understanding of the practical effects of portfolio management in the public sector and outline a set of practices already tried by municipal administrators, which can be replicated.